2016
DOI: 10.1177/0971890716670707
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Linkage between Profits and Asset–Liability Management

Abstract: The article uses panel data regression on a sample of 26 public sector and 20 private sector banks operating in India over the period 2004–2005 to 2012–2013 in order to empirically examine the relationship between profits and asset–liability (A–L) composition of Indian banks. The sample was initially split into public sector and private sector banks. Earning before tax (EBT) of public sector banks appear to be generated by all the assets under the asset portfolio while, in private sector banks, the EBT seems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
2
5
1
Order By: Relevance
“…This suggests that consistent with findings Vasiliou (1996), return on asset is higher for banks with high profit levels than for banks with low profit levels. While this is inconsistent with the findings of Kwast and Rose (1982) and Kosmidou et al (2004), the observations are consistent with evidence by Chatterjee and Dutta (2016) in the Indian banking sector. Loans to customer (A1) are the highest earning assets for Low‐profit banks whilst other assets (A6) earn the highest rate of returns for High‐profit banks.…”
Section: Resultscontrasting
confidence: 91%
See 3 more Smart Citations
“…This suggests that consistent with findings Vasiliou (1996), return on asset is higher for banks with high profit levels than for banks with low profit levels. While this is inconsistent with the findings of Kwast and Rose (1982) and Kosmidou et al (2004), the observations are consistent with evidence by Chatterjee and Dutta (2016) in the Indian banking sector. Loans to customer (A1) are the highest earning assets for Low‐profit banks whilst other assets (A6) earn the highest rate of returns for High‐profit banks.…”
Section: Resultscontrasting
confidence: 91%
“…On the contrary, Lower‐profit banks are observed to experience higher cost on fixed deposits (L3), other short‐term funds (L5) and long‐term liabilities (L6). While similar results were reported by Chatterjee and Dutta (2016), this finding contradicts Vasiliou (1996) and Kosmidou et al (2004) who reported lower cost of funding for high‐profit banks.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Most banks in international economies started strategic planning for asset and liabilities management in the 1970s (Goodman & Langer, 1983). At that time, Indian banks were free from interest rate risk as it was regulated and governed by the Reserve Bank of India (Chatterjee & Dutta, 2016). When other economies were planning for deregulation and Asset-Liability Management (ALM), Indian banks were getting nationalization (in 1969).…”
Section: Introductionmentioning
confidence: 99%